Pengaruh model project based learning terhadap berpikir kritis peserta didik - Ghina Faridah Wirawan; Peduk Rintayati; Chumdari Chumdari (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2024)
One important skill that must be developed through school is critical thinking. The use of project-based learning strategies is one technique for improving critical thinking skills. This research seeks to determine the impact of the project-based learning model on students' critical thinking abilities, as well as the effect of implementing the model on these abilities. In addition, this research aims to determine the extent of the influence of the project-based learning model on students' critical thinking abilities at SD Gugus 3 Laweyan Surakarta. This research uses a quasi-experimental design and quantitative methodology. This research uses a pretest-posttest control group design as the research methodology. There are two classes that are the research sample, namely Class 5 and Class 6.